Improvement of tinnitus, anxiety, and depression following cochlear implant surgery: a prospective cohort study - Lamounier, Pauliana; Gonçalves, Victória Franco; Queiroz, Isabela Carvalho; Gobbo, Débora Aparecida; Bernardes, Marina Nahas Dafico; Costa, Claudiney Cândido; Ramos, Hugo Valter Lisboa; Bahmad, Fayez (Frontiers in Audiology and Otology, 2024)
Introduction: Hearing loss affects approximately 1.5 billion people worldwide and is the greatest risk factor for tinnitus, a condition that can further worsen quality of life, lead to high anxiety and depression, and affect general health and well-being. Objectives: To assess the impact of cochlear implants (CIs) on tinnitus perception and quality of life and their relationship with psychological disorders, such as depression and anxiety. Methods: Thirty adults with profound bilateral hearing loss who were candidates for CI surgery and who experienced tinnitus were assessed using the Tinnitus Handicap Inventory (THI), the Visual Analogue Scale (VAS), the WHOQOL-BREF, and the Hospital Anxiety and Depression Scale (HADS) questionnaires at 4 different time points: preoperatively, 7 days after cochlear implant activation, and 3 and 6 months after cochlear implant surgery. The International Outcome Inventory CI (IOI-CI) was applied at 3 and 6 months, and the Glasgow Benefit Inventory (GBI) questionnaire was applied at 6 months. Results: VAS and THI scores improved; however, significant improvements were only observed in THI scores 6 months post-surgery. Time spent using hearing aids did not correlate significantly with speech recognition test scores, nor were there significant correlations between the changes in the preoperative THI score and VAS scores or the changes in the speech recognition test scores 6 months post-surgery. We observed a decrease in anxiety and depression scores at the 6-month follow-up compared with the preoperative period. Conclusion: THI scores significantly increased after CI surgery, suggesting that tinnitus improved. Trends in improved anxiety and depression scores after CI surgery were also observed. Scores associated with the WHOQOL-BREF quality of life self-evaluations, and the environment and general domains, significantly improved.